Implementação dos programas de fortalecimento dos Conselhos escolares na Rede Pública de Ensino de Uberlândia - 2014/2015 - Sousa, Enise Cristina Barbaresco de (2016)
This work is part of a process of investigation made with the Post-Graduation Education Program of UNIVERSIDADE FEDERAL DE UBERLANDIA, in the research line of State, Politician and Education Management. The main purpose is analyze the guidelines and make the School Boards stronger, with good proposals , and study your implementation in public schools in the city of Uberlandia while democratization mechanisms through the creation and execution from the categories participation, democratic governance and citizenship. The research starts questioning educational problems of creation and fortification School Boards, this Counsel guide the practice and analyze the viability to effect these proposals. The methodological approach of this work traces back the process of elaboration and implementation of Counsel of School for the democratization of school management that supports in theoretical productions already made about the object. We analyze the implementation of Counsel of School in six schools of city Uberlandia in 2014 and 2015, we done a qualitative approach employing the use of documentary research, in the national, state and local sphere. The research shows the way of how the educational system is organized, the conditions of work that are offered to professionals in Brazil culture, among other factors, the acting of School Boards cannot accomplish all the responsibilities that the regulatory context predict. The conclusion of this work shows that School Boards contribute to the democratization management and for exercise citizenship, but there is no warranty of this practice, because everything depends of other mechanisms of participation and the interests of all involved sectors.